English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

what is the derivative, and how do you take the derivative of the following?

y= 3( 2x^(-1/2) + 1)^(-1/3)

that reads "three times the quantity two-x to the negative one-half plus one, quantity to the negative one-third."

i hope that's how it reads at least....

2007-02-18 05:29:27 · 4 answers · asked by tmrrwtdy 1 in Science & Mathematics Mathematics

4 answers

Start with

f(x)=3
g(x)=(2x^(-1/2)+1)^(-1/3)

We know that f'(x)=0, but we need to expand on the g'(x):

(2x^(-1/2)+1)^(-1/3):

For this funcion, let

f(x)=x^(-1/3)
g(x)=2x^(-1/2)+1

Then f'(x)=(-1/3)x^(-4/3)
and g'(x)=-x^(-3/2)

Because this is a composite function, we need to use the formula

f'(g(x))*g'(x)

So we get

(1/3)x^(-3/2)*
(2x^(-1/2)+1)^(-4/3)

for our g'(x) in our original function. To combine everything, we need to use the product rule, so for

y= 3( 2x^(-1/2) + 1)^(-1/3)

f(x)=3
f'(x)=0
g(x)=(2x^(-1/2)+1)^(-1/3)
g'(x)=(1/3)x^(-3/2)*
(2x^(-1/2)+1)^(-4/3)
(solved from above)

The product rule is the formula:

f'(x)g(x)+f(x)g'(x)

So your final solution will be

x^(-3/2)(2x^(-1/2)+1)^(-4/3)

2007-02-20 06:02:56 · answer #1 · answered by Crystal 3 · 0 0

Use the power rule and chain rule...

y' = -(2x^(-1/2)+ 1)^(-4/3) *( -1(x^(-3/2)))

(I'm not 100% on this one though)

2007-02-18 13:34:26 · answer #2 · answered by Anonymous · 0 0

the answer is
1 over x(x^.5 +2)((x^.5 +2)/x^.5)^(1/3)

my TI-89 gave me that answer.. I got lost trying to work it out by hand.. i hope this kind of gives you a guideline

2007-02-18 13:37:48 · answer #3 · answered by Sum Girl 4 · 0 0

You need to use the function of a function rule. You start by rewriting it as y = 3z^(-1/3) and differentiate that. Then you multiply by dz/dx.

2007-02-18 13:35:52 · answer #4 · answered by mathsmanretired 7 · 0 0

fedest.com, questions and answers